Hardness Characteristics of as-cast Ni-Ru-Zr Alloys - Chipise, Liberty; Batane, Robert; Jain, Pushpendra K.; Coetzee, Stephan H.; Odera, Bernard O.; Goosen, William; Cornish, Lesley A. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
The Vickers hardnesses of 21 as-cast Ni-Ru-Zr alloys of different compositions were studied, and nanohardness indentations were done on the individual phases. The results were used to explain the brittleness by assessing the proportions of the phases, and their morphologies. The compound hardnesses varied between 704 – 1289 HV, with ~ZrRu2 being the hardest phase, and ~Zr2Ni7 being the least hard phase. The sample hardnesses were 300 - 1015 HV. Most of the samples were brittle, although there were regions of toughness around Ni36:Ru13:Zr51 and Ni20:Ru5:Zr75 (at.%). No alloy was identified to have potential good mechanical properties.
Keywords: Hardness; Ni-Ru-Zr; Alloys; Phase diagram; Ternary